Flexural characterization and ductility assessment of small-scale mortar beams reinforced with 3D-printed polymers. (November 2022) - Talha Junaid, M.; Shweiki, Ahmed; Barakat, Samer; Alhalabi, Mohamad; Mostafa, Omar
Abstract: Additive Manufacturing (AM) is recently getting tremendous attention in many scientific fields. In this research, a civil engineering application of AM is investigated, where thirty small-scale cement mortar prisms reinforced with 3D-printed thermoplastics were tested in flexure. Rebar-like reinforcement were printed using a fused deposition modeling (FDM) printer. Five different thermoplastics were used with three different surface morphologies, obtained by introducing lugs on the rebar surface. The lugs were intended to enhance the reinforcement-matrix bond. Beams were tested in a three-point bending configuration to assess their load–deflection response and flexural ductility. In general, the introduction of lugs increased the load-carrying capacity of the specimen, between 40 and 120%. The ductility of beams was calculated based on displacement and energy methods. Due to the lack of a definite yield point in such composites, modifications to well-established ductility calculation methods are proposed here. The results indicate the capability of thermoplastics to reinforce mortar beams in flexure. Surface morphology has shown to be significantly influential for most of the thermoplastics considered in this study in terms of strength gain and ductility.